The Invisible Web : uncovering information sources search engines can't see - Sherman, Chris, 1958- (CyberAge Books, 2001)
Enormous expanses of the Internet are unreachable with standard web search engines. This book provides the key to finding these hidden resources by identifying how to uncover and use invisible web resources. Mapping the invisible Web, when and how to use it, assessing the validity of the information, and the future of Web searching are topics covered in detail. Only 16 percent of Net-based information can be located using a general search engine. The other 84 percent is what is referred to as the invisible Webmade up of information stored in databases. Unlike pages on the visible Web, information in databases is generally inaccessible to the software spiders and crawlers that compile search engine indexes. As Web technology improves, more and more information is being stored in databases that feed into dynamically generated Web pages. The tips provided in this resource will ensure that those databases are exposed and Net-based research will be conducted in the most thorough and effective manner.